Selective phptocatalytic oxidation of aromatic alcohols with titanium dioxide - Yurdakal, Sedat (Anadolu Üniversitesi, 2010)
Home-prepared (HP) TiO2 catalysts were prepared by sol-gel process and characterized by using XRD, SEM and BET methods. They were used in a batch photoreactor for performing the selective oxidation of 4-methoxybenzyl alcohol to 4-methoxybenzaldehyde in water. Then by using the most selective photocatalyst, 4-substitute aromatic alcohols were oxidised to corresponding aldehydes in order to investigate the influence of the substituent group on the reaction rate and selectivity. Commercial TiO2 catalysts were also used for comparison. HP TiO2 catalysts showed selectivity 3-8 times higher than commercial catalysts. The Hammett relationship well describes the influence of substituent group on the kinetic constant of partial oxidation to aldehydes. Moreover a continuous annular fixed bed photoreactor containing Pyrex beads covered by HP TiO2 was investigated for the same reaction. The Langmuir-Hinshelwood approach was satisfactorily applied for modelling the photoreactivity results and the values of all the model parameters were determined. Selectivity enhancement by aliphatic alcohols was investigated; the addition of an aliphatic alcohol in small amounts decreased the overall oxidation rate but enhanced the selectivity for aldehyde formation up to 1.5 times. The values of band gap, valence band and conduction band edges are similar for all the samples. The ATR-FTIR investigation indicates that HP and Degussa P25 TiO2 surfaces show a very dissimilar hydrophilicity and different ability for adsorbing the organic compounds deriving from benzyl alcohol oxidation. Finally, this thesis presents a quantitative method which enables to determine the amount of substrate photoadsorbed onto the catalyst surface in the same reaction conditions. The method is applied to oxidation of phenol in the presence of Degussa P25 and oxidation of benzyl alcohol in the presence of a HP catalyst. The influence of substrate concentration, catalyst amount and irradiation power on photoadsorption is investigated by using Langmuir, Freundlich, and Redlich-Peterson isotherms. All the parameters of kinetic model are favorably affected by an increase of the photon flow absorbed per unit mass of catalyst.
Keywords: Fotokataliz; Titanyum dioksit; Aromatik alkoller; Seçici oksidasyon; Fotoadsorpsiyon; Sürekli silindirik sabit yataklı fotoreaktör